Pelaksanaan Pembimbingan dan Pengawasan Klien Asimilasi Covid-19 di Balai Pemasyarakatan Kelas II Garut - Pertiwi, Regita Mauldi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The emergence of a very dangerous country at this time has made the world experience the effects of epidemics in various fields. This pandemic is happening in every country in the world. This outbreak is known as the Covid-19 Pandemic or Corona Virus Disease (covid-19). As a form of preventing the spread of the corona virus in Correctional Institutions, the Directorate General of Corrections through Circular of the Director General of Corrections Number: PAS-20.PR.01.01 of 2020 concerning Progressive Steps to Overcome the Spread of Corona Virus (Covid-19) in Correctional Technical Implementing Units in the form of assimilation and integration. In terms of supervising and supervising supervision and children, the Penitentiary Refers to a Community Advisor to carry out this obligation online. This study aims to provide an explanation of the function of the Correctional Center as well as efforts to optimize it even as a supervising institution that is assimilated at home in the Covid-19 pandemic situation. The study was conducted using qualitative methods by observation at the Garut Class II Correctional Center. The results of this study found that the correctional center was optimal in guiding and supervising the assimilation and integration of Covid-19 clients.